2022
DOI: 10.3390/data8010013
|View full text |Cite
|
Sign up to set email alerts
|

A Consistent Land Cover Map Time Series at 2 m Spatial Resolution—The LifeWatch 2006-2015-2018-2019 Dataset for Wallonia

Abstract: Ecosystem accounting is based on the definition of the extent and the status of an ecosystem. Land cover maps extents are representative of several ecosystems and can therefore be used to support ecosystem accounting if reliable change information is available. The dataset described in this paper aims to provide land cover information (13 classes) for biodiversity monitoring, which has driven two key features. On one hand, open areas were described in more details (5 classes) than in the other maps available i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…We got an overview of the landscape available for ME by calculating the relative area of nine land cover classes within a 10 km radius around each breeding colony (Figs 1 and 2 ; see the S1 File for the explanation of the land cover classification). Classes were estimated using the LifeWatch Landcover database from 2015 [ 64 ] and QGIS tools (v3.28; QGIS Development Team). We selected this distance as it was previously reported that ME may forage up to about 10 km from their breeding colony [ 35 , 51 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…We got an overview of the landscape available for ME by calculating the relative area of nine land cover classes within a 10 km radius around each breeding colony (Figs 1 and 2 ; see the S1 File for the explanation of the land cover classification). Classes were estimated using the LifeWatch Landcover database from 2015 [ 64 ] and QGIS tools (v3.28; QGIS Development Team). We selected this distance as it was previously reported that ME may forage up to about 10 km from their breeding colony [ 35 , 51 , 59 ].…”
Section: Methodsmentioning
confidence: 99%